Strategi Kaprodi Dalam Mewujudkan Mutu Prodi PAI Pada Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri - Giagi Rachmoyo; Reza Ahmad Zahid; Badrus Badrus (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
The learning and teaching system at the Postgraduate level of higher education greatly contributes to the development of society and the state. Postgraduate class must certainly have a good strategy in improving the quality of education. so that the results obtained are in accordance with the goals that have been outlined. Likewise, the Postgraduate Program system at the Tribakti Islamic University Lirboyo Kediri. no exception to the Education. However, efforts to realize Quality in the Study Program play an important role in making it happen. This study aims to determine the form of caprodi strategy in realizing the quality of PAI Study Program at the Postgraduate Program of Tribakti Islamic University, knowing the procedures of each Kaprodi strategy in Realizing the Quality of PAI Study Program at the Postgraduate Program of Tribakti Islamic University. The method used in this research is descriptive qualitative with the type of field research approach. This research was conducted at Tribakti Islamic University (UIT) Lirboyo Kediri, Lirboyo Darussalam Islamic Boarding School, Kediri. The results of this study are: 1) The form of Kaprodi's Strategy in realizing the Quality of PAI Study Program at the Postgraduate Program of Tribakti Islamic University has several forms, namely by Achieving Accreditation-Based Quality, Preserving Excellent Programs and International Proceedings Seminars. 2) Quality planning, quality control and quality improvement. The procedure includes three activities, namely opening activities such as debriefing and grouping students with lecturers. In this core activity is carried out while the activity is in progress such as making observations. for closing activities carried out at the end of the activity and after activities such as making final reports in the form of journals and articles which are used as a condition for the completion of the activity. Of the three contain Quality Planning, Quality Quality and Quality Improvement.